Characterization of Site-Directed Mutants in the Cytochrome c-550 Protein of Photosystem II - Manne, Akarsh (East Carolina University, 2010)
Photosynthesis is the process by which cyanobacteria, algae, and higher plants convert light energy to chemical energy via the biosynthesis of carbohydrates. Photosystem II is a multi-protein/pigment complex embedded in the thylakoid membrane. CP43 is the product of the psbC gene, and is an intrinsic component of the photosystem II complex. CP43 is 473 amino acids long and has five hydrophilic loops connecting six transmembrane alpha helices, including a large extrinsic loop E which is exposed to the lumenal side of the thylakoid membrane. Short deletions of regions of the loop E of CP43 resulted in mutants that fail to grow photoautotrophically and are devoid of oxygen-evolving activity. A mutation was introduced in loop E that altered arginine at position 305 to a serine residue, producing a mutant with severely reduced growth and oxygen evolving activity under chloride limiting conditions. However, when grown under normal conditions, the R305S mutant showed no extreme phenotype. After isolation of photosystem II particles and chemilumininescent staining for cytochromes, it was determined that this specific mutation resulted in loss of binding of an extrinsic photosystem II protein, cytochrome c-550. Deletion of the psbV gene encoding cytochrome c-550 resulted in the loss of photoautotrophic growth in media lacking chloride and/or calcium. X-ray crystallography of photosystem II does in fact show a close proximity between cytochrome c-550 and CP43. Based on the crystal structure, two residues on cytochrome c-550 were identified that might interact with CP43 and are in close proximity with the arginine residue at position 305. These residues on cytochrome c-550 are both highly conserved asparagines, located at positions forty nine and fifty one. In this work, the asparagine residue at position fifty one on cytochrome c-550 was mutated to either an alanine or aspartic acid residue. The N51 mutations were transformed into wildtype Synechocystis, a cyanobacterial model organism that has been widely used to study photosystem II. The N51 mutants were characterized by photoautotrophic growth in complete and chloride-limiting media, oxygen evolution assays, variable florescence yield measurements and photoinactivation assays. Based on these assays, the control and N51 mutant strains exhibited similar phenotypes in complete media while the control and N51D mutant strains exhibited similar phenotypes in chloride limiting media. The N51A mutant had a small but reproducible decrease in photoautotrophic growth rate, oxygen evolution rates and enhanced sensitivity to photoinactivation in chloride limiting media. Therefore, asparagine at position fifty one on cytochrome c-550 might contribute to a weak interaction between arginine on CP43 and cytochrome c-550, which is likely to involve hydrogen bonding. However, further studies are needed to validate the proposed interaction between subunits cytochrome c-550 and CP43 of photosystem II.
Keywords: Biology, Molecular; Molecular biology; Photosynthesis--Genetic aspects; Mutation (Biology)